Novel and Green Fe3O4@Sio2-L-Cys Magnetic Absorbent for Efficient Removal of Pb (II) from Aqueous Solution. Issue 1 (1st February 2022) - Su, X D; Huang, E; Cheng, Z; Su, Y; Zhong, Y H; Deng, X
Abstract: In this study, Fe3 O4 @Sio2 -NH2 was synthesized by the modification of Fe3 O4 particles with tetraethyl orthosilicate(TEOS) and 3-aminopropyl-Triethoxysilane (APTES), and then the cysteine was grafted with glutaraldehyde as cross-linking agent.The material was characterized by XRD, FIIR and TEM. The effects of temperature, time, initial concentration of Pb(II) and pH value on the adsorption rate of Pb(II) were investigated, and the adsorption mechanism and the regeneration performance of the adsorbent were discussed.The results indicated that when the amount of adsorbent was 0.4g/L, the temperature was 303K, the adsorption time was 2.5h and the pH was 5.02, the adsorption rate of Pb(II) in water can reach up to 98.25%.The adsorption kinetics of Pb(II) on the material accorded with Lagergren quasi-second-order kinetic equation, which belonged to the chemisorption process.Adsorption isothermal curve studies showed that the adsorption of Pb(II) on the material complied with the Langmuir isothermal adsorption model and was a monolayer adsorption.The maximum adsorption capacity of Pb(II) is 120.77mg/g. Adsorption thermodynamics studies showed that the whole system was endothermic reaction, and warming was conducive to the adsorption, which happens spontaneously.After 4 times of the adsorption recycling, the adsorption rate can still reach 92.7%.